Long-term use of interferon-β in multiple sclerosis increases Vδ1(−)Vδ2(−)Vγ9(−) γδ T cells that are associated with a better outcome - Maimaitijiang, Guzailiayi (J Neuroinflammation, 2019)
BACKGROUND: We previously reported that Vδ2(+)Vγ9(+) γδ T cells were significantly decreased in multiple sclerosis (MS) patients without disease-modifying therapies (untreated MS) and were negatively correlated with Expanded Disability Status Scale (EDSS) scores, suggesting protective roles of Vδ2(+)Vγ9(+) γδ T cells. Interferon-β (IFN-β) is one of the first-line disease-modifying drugs for MS. However, no previous studies have reported changes in γδ T cell subsets under IFN-β treatment. Therefore, we aimed to clarify the effects of the long-term usage of IFN-β on γδ T cell subsets in MS patients. METHODS: Comprehensive flow cytometric immunophenotyping was performed in 35 untreated MS and 21 MS patients on IFN-β for more than 2 years (IFN-β-treated MS) including eight super-responders fulfilling no evidence of disease activity criteria, and 44 healthy controls (HCs). RESULTS: The percentages of Vδ2(+)Vγ9(+) cells in γδ T cells were significantly lower in untreated and IFN-β-treated MS patients than in HCs. By contrast, the percentages of Vδ1(−)Vδ2(−)Vγ9(−) cells in γδ T cells were markedly higher in IFN-β-treated MS patients than in HCs and untreated MS patients (both p < 0.001). A significant negative correlation between the percentages of Vδ2(+)Vγ9(+) cells in γδ T cells and EDSS scores was confirmed in untreated MS but not evident in IFN-β-treated MS. Moreover, class-switched memory B cells were decreased in IFN-β-treated MS compared with HCs (p < 0.001) and untreated MS patients (p = 0.006). Interestingly, the percentages of Vδ1(−)Vδ2(−)Vγ9(−) cells in γδ T cells were negatively correlated with class-switched memory B cell percentages in all MS patients (r = − 0.369, p = 0.005), and the percentages of Vδ1(−)Vδ2(−)Vγ9(−) cells in Vδ1(−)Vδ2(−) γδ T cells were negatively correlated with EDSS scores only in IFN-β super-responders (r = − 0.976, p < 0.001). CONCLUSIONS: The present study suggests that long-term usage of IFN-β increases Vδ1(−)Vδ2(−)Vγ9(−) γδ T cells, which are associated with a better outcome, especially in IFN-β super-responders. Thus, increased Vδ1(−)Vδ2(−)Vγ9(−) cells together with decreased class-switched memory B cells may contribute to the suppression of disease activity in MS patients under IFN-β treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-019-1574-5) contains supplementary material, which is available to authorized users.